ALGORITHM OF CALCULATION OF LYAPOUNOV COEFFICIENTS FOR ANALYSIS OF CHEMICAL AUTOOSCILLATIONS, AS APPLIED TO CALCITE CRYSTALLIZATION MODEL - Bryxina N.A.; Sheplev V.S. (My University, 2001)
The numerical algorithm of calculation of Lyapounov coefficients (L k) of any order is developed. The apparatus of analytical calculations is not used in this algorithm. The proposed algorithm is of use for usual computer languages and allows us to find the numerical value of L k for any k and to make complete qualitative analyses of dynamic models on the plane.